Development And Validation Of A Sensitive Reversed-Phase Hplc Method For The Determination Of Monothioglycerol In Bulk And In Its Pharmaceutical Formulation - D.PEER BASHA; K. RAVI SHANKAR; G.V.N.KIRANMAYI (International Journal of Pharma and Bio Sciences, 2012)
A rapid and sensitive RP-HPLC method with UV detection at 205 nm for routine analysis of Monothioglycerol in bulk and pharmaceutical formulations was developed. Chromatography was performed with mobile phase containing a mixture of acetonitrile and 0.01Mphosphate buffer in the ratio of 5:95, v/v with flow rate 1.0 ml/min. The calibration graph of Monothioglycerol was found to be linear over the range of 0.5 to1.5 mg/ml with correlation coefficient of 0.99. Sensitivity, accuracy, range, precision, robustness, ruggedness, stability, specificity, limit of detection, limit of quantification and system suitability parameters were validated for the developed method. The developed method was successfully applied to estimate the amount of Monothioglycerol in injection formulations.